Carotenoid metabolism in mammals, including man: formation, occurrence, and function of apocarotenoids: Thematic Review Series: Fat-Soluble Vitamins: Vitamin A - Eroglu, Abdulkerim (The American Society for Biochemistry and Molecular Biology, 2013)
Vitamin A was recognized as an essential nutrient 100 years ago. In the 1930s, it became clear that dietary β-carotene was cleaved at its central double to yield vitamin A (retinal or β-apo-15′-carotenal). Thus a great deal of research has focused on the central cleavage of provitamin A carotenoids to form vitamin A (retinoids). The mechanisms of formation and the physiological role(s) of noncentral (eccentric) cleavage of both provitamin A carotenoids and nonprovitamin A carotenoids has been less clear. It is becoming apparent that the apocarotenoids exert unique biological activities themselves. These compounds are found in the diet and thus may be absorbed in the intestine, or they may form from enzymatic or nonenzymatic cleavage of the parent carotenoids. The mechanism of action of apocarotenoids in mammals is not fully worked out. However, as detailed in this review, they have profound effects on gene expression and work, at least in part, through the modulation of ligand-activated nuclear receptors. Understanding the interactions of apocarotenoids with other lipid-binding proteins, chaperones, and metabolizing enzymes will undoubtedly increase our understanding of the biological roles of these carotenoid metabolites.